2019
DOI: 10.1007/s00221-019-05662-4
|View full text |Cite
|
Sign up to set email alerts
|

Robot controlled, continuous passive movement of the ankle reduces spinal cord excitability in participants with spasticity: a pilot study

Abstract: Spasticity of the ankle reduces quality of life by impeding walking and other activities of daily living. Robot-driven continuous passive movement (CPM) is a strategy for lower limb spasticity management but effects on spasticity, walking ability and spinal cord excitability (SCE) are unknown. The objectives of this experiment were to evaluate (1) acute changes in SCE induced by 30 min of CPM at the ankle joint, in individuals without neurological impairment and those with lower limb spasticity; and, (2) the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…In recent years, there has been a great deal of attention paid to research on enhancement methods of RI to inhibit excessive simultaneous activity and to inhibit the excitability of antagonist muscles (Fujiwara et al., 2011; Hirabayashi, Edama, Kojima, Miyaguchi, & Onishi, 2019; Jessop, DePaola, Casaletto, Englard, & Knikou, 2013; Kubota, Hirano, Morishita, Uehara, & Funase, 2015; Noble, Pearcey, Quartly, & Zehr, 2019; Perez, Field‐Fote, & Floeter, 2003; Ritzmann, Krause, Freyler, & Gollhofer, 2018; Roche, Lackmy, Achache, Bussel, & Katz, 2009, 2011; Yamaguchi et al., 2016, 2018). At our research institute, we have previously reported on the influence of repetitive passive movement (RPM) on the cerebral cortex, with RPM currently used widely as a rehabilitation technique (Miyaguchi et al., 2013; Sasaki et al., 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a great deal of attention paid to research on enhancement methods of RI to inhibit excessive simultaneous activity and to inhibit the excitability of antagonist muscles (Fujiwara et al., 2011; Hirabayashi, Edama, Kojima, Miyaguchi, & Onishi, 2019; Jessop, DePaola, Casaletto, Englard, & Knikou, 2013; Kubota, Hirano, Morishita, Uehara, & Funase, 2015; Noble, Pearcey, Quartly, & Zehr, 2019; Perez, Field‐Fote, & Floeter, 2003; Ritzmann, Krause, Freyler, & Gollhofer, 2018; Roche, Lackmy, Achache, Bussel, & Katz, 2009, 2011; Yamaguchi et al., 2016, 2018). At our research institute, we have previously reported on the influence of repetitive passive movement (RPM) on the cerebral cortex, with RPM currently used widely as a rehabilitation technique (Miyaguchi et al., 2013; Sasaki et al., 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sphericity was assumed via Mauchly's Test (p > 0.05) and if not, degrees of freedom and p-value were corrected using the Greenhouse-Geisser method. When there were no differences between the pre-intervention results, an averaged pre-intervention value was compared to the post-intervention results using a paired t-test, as done in previous training studies [25][26][27]. The difference between post and baseline values were expressed as percent change from the pre-intervention results (%∆).…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…While the upright position is ideal for matching training conditions, group Ia presynaptic inhibition is modulated in this posture [49][50][51]. Since changes in re ex amplitude due to training in other work [27] shows Ia PSI as a mechanism of neuroplasticity, our choice of standing may have weakened our ability to detect change. Future work should include re ex measurement across a variety of tasks from sitting, standing, and walking [49] to better assess any changes in re ex excitability.…”
Section: Spinal Cord Excitability After 5-weeks Of Trainingmentioning
confidence: 99%
See 2 more Smart Citations